2022
DOI: 10.3389/fimmu.2021.753412
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus Alleviates Renal Allograft Interstitial Fibrosis by Inhibiting Epithelial-to-Mesenchymal Transition Not Only via Inducing Autophagy but Also via Stabilizing IκB-α

Abstract: Chronic allograft dysfunction (CAD) is the major cause of late graft loss in long-term renal transplantation. In our previous study, we found that epithelial–mesenchymal transition (EMT) is a significant event in the progression of renal allograft tubulointerstitial fibrosis, and impaired autophagic flux plays a critical role in renal allograft fibrosis. Everolimus (EVR) has been reported to be widely used to prevent the progression of organ fibrosis and graft rejection. However, the pharmacological mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…Our previous research revealed that ATG16L‐dependent autophagy deficiency fostered the progression of EndMT and renal fibrosis after kidney transplantation 12 . Furthermore, we discovered that everolimus was capable to restoring autophagic flux, thus diminishing renal allograft interstitial fibrosis via the inhibition of the mTOR pathway 45 . In our study, we affirmed that BNIP3 knockdown negates the augmented mitophagy, and reverses the amelioration in ECM deposition and EndMT induced by Rictor ablation in endothelial cells after kidney transplantation.…”
Section: Discussionsupporting
confidence: 69%
“…Our previous research revealed that ATG16L‐dependent autophagy deficiency fostered the progression of EndMT and renal fibrosis after kidney transplantation 12 . Furthermore, we discovered that everolimus was capable to restoring autophagic flux, thus diminishing renal allograft interstitial fibrosis via the inhibition of the mTOR pathway 45 . In our study, we affirmed that BNIP3 knockdown negates the augmented mitophagy, and reverses the amelioration in ECM deposition and EndMT induced by Rictor ablation in endothelial cells after kidney transplantation.…”
Section: Discussionsupporting
confidence: 69%
“…Increasing evidence reveal that Akt/mTOR and NF-κB activation upregulates renal inflammation and dramatically promotes renal interstitial fibrosis and fibroblast activation [ 47 50 ]. And upregulation of autophagy upon PI3K/Akt/mTOR pathway inhibition can significantly stabilize IκB-α and reduce the expression of TNF-α-induced EMT [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that in ammation response contributes to the development of EMT, which plays a crucial role in driving the PF development [51,52]. It has been reported that TNF-α induced EMT was through activation of Akt/NF-κB (nuclear factor kappa B) pathway in a renal allograft interstitial brosis [53]. In addition, IL-1β signi cantly upregulated the expressions of MMP-2 as well as EMT markers, such as vimentin, α-SMA, bronectin [54].…”
Section: Discussionmentioning
confidence: 99%